Nucleolar and cytoplasmic RNA density-concentration in leukemia granulocytic progenitors in human bone marrow biopsies: A short cytochemical note - Smetana, Karel; Jirásková, Ilona; Mikulenková, Dana; Klamová, Hana (Acta histochemica, 2011)
The present study was undertaken to provide more information on the differentiation and maturation of human granulocytes using computer-assisted image RNA densitometry at single-cell level. The bone marrow of patients suffering from chronic phase of chronic myeloid leukemia represents a very convenient model for such measurements because of the satisfactory number of early stages, as well as advanced stages, of the granulocytic cell lineage represented by neutrophils. In contrast to the erythroid cell lineage, similar nucleolar and cytoplasmic RNA density-concentration values were found only in early granulocytic progenitors such as myeloblasts and promyelocytes. In advanced stages of the granulocytic development starting with myelocytes, these cells were characterized by a larger decrease in the cytoplasmic RNA concentration in comparison with that of the nucleoli. Thus, the nucleolar to cytoplasmic RNA concentration ratio in these cells was above 1. On the other hand, it should be pointed out that late differentiation stages of granulocytes, starting with myelocytes, possessed nucleolar bodies (nucleoli without surrounding perinucleolar chromatin) of a markedly reduced size.
Keywords: buněčná diferenciace; Biopsy; Granulocyte Precursor Cells; Humans; buněčný rodokmen; RNA; Chronic Disease; lidé; Cell Nucleolus; Densitometry; Cell Lineage; počítačové zpracování obrazu; velikost částic; Image Processing, Computer-Assisted; biopsie; chronická nemoc; Cytoplasm; Cell Differentiation; cytoplazma; denzitometrie; Leukemia, Myeloid; Particle Size; prekurzorové buňky granulocytů; myeloidní leukemie; buněčné jadérko